METHODS OF USING MONTMORILLONITE FOR WATER PURIFICATION - Erimbatova Dilnoza Nurulla qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: Montmorillonite, a type of smectite clay mineral, has proven to be an effective natural adsorbent in water purification due to its high surface area, cation exchange capacity, and swelling properties. This article reviews the various methods of applying montmorillonite for the removal of contaminants such as heavy metals, dyes, and organic pollutants from water. Different modification techniques that enhance its adsorption efficiency and regeneration potential are also discussed.